EVALUASI PENGGUNAAN ANTIBIOTIK PROFILAKSIS PADA PASIEN BEDAH DI SALAH SATU RUMAH SAKIT KOTA BANDUNG - Ida Lisni (Universitas Bhakti Kencana, 2014)
Surgery is a treatment on a part of the body that can cause infections. One of the factor that can decrease the number of surgical infections by administering the antibiotic propylaxis. Antibiotic propylaxis that used must be safe,bacterisid and effective againts bacteria. this research aimd to know the appropriateness of antibiotics for surgical propylaxis that includesaccuracy of diagnose, accuracy of dosage and timeliness of administering of antibiotics. A method of this study using data retrospective include determinations criteria of drugs, patients and standars medical use. The data obtainedfrom the medical record was evaluated of medical record reliability according to criteria of the use of antibiotics that were made. Based on the result of the study the number of patients who underwent surgery with details 30 man and 54 woman and the propylaxys antibiotic that used was the third generations of cephalosporin (90,84%) having broad spectrum and effective againts gram positive and negative bacteria. From the data has been evaluated there was glaring discrepancy in provisions of prophylaxys antibiotics 4,77%. but for the accuracy of the diagnosis, dose and mode of administration of antibiotic prophylaxis is in compliance with the criteria of the use of prophylaxys antibiotics. We concluded that the use of antibiotics as a prophylactic surgery were in accordance with the criteria of the use of antibiotics as a prophylactic surgery. Keywords: , , Kata Kunci : , ,